Controle de veículos aéreos não tripulados transportando cargas suspensas - Pizetta, Igor Henrique Beloti (2019)
The use of unmanned aerial vehicles (UAVs) to perform tasks is already a reality. These vehicles have great versatility, so that they can be used in several applications, such as in load transportation. In this Doctoral Thesis two load-carrying systems are proposed, with the use of one or two vehicles for transporting a load suspended by cables. As the load is free in the space, limited by the connection with the UAVs, oscillations occur due to its inertia, which affect the flight of the vehicles due to the transmission of forces to the vehicles connected by the cables. Mathematical models are developed starting from the Euler-Lagrange equations, and a nonlinear controller is proposed to guide the systems in the accomplishment of flight tasks, rejecting the disturbance generated by the load. In addition, the developed systems have the ability to avoid obstacles in their path. As an extra feature of the cooperative system, a potential field is proposed to prevent the vehicles of approaching during positioning tasks, thus preserving flight safety. First, the models and controller presented deal with navigation in a plane (PVTOL - Planar Vertical Takeoff and Landing). Next, we present the models and controller for the systems when navigating in three-dimensional space, with flight tasks corresponding to positioning and trajectory tracking, in addition to the combination with obstacle avoidance.